2021
DOI: 10.1155/2021/5551216
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Fat Percentage with Time in Range Generated by Continuous Glucose Monitoring during Continuous Subcutaneous Insulin Infusion Therapy in Type 2 Diabetes

Abstract: Background. Obesity is a crucial risk factor associated with type 2 diabetes mellitus (T2DM). Excessive accumulation of body fat may affect the glycemia control in T2DM. This study investigated the relationship between body fat percentage and time in range (TIR) assessed by continuous glucose monitoring (CGM) during short-term continuous subcutaneous insulin infusion (CSII) therapy in T2DM patients. Method. A total of 85 T2DM patients were recruited in this cross-sectional study. All participants underwent 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To date, only one cross‐sectional study done in China has reported the association between HbA1c and body fat percentage in T2DM patients on insulin therapy. In this study, a Jawon bioelectrical impedance analyzer (BIA) was used to measure body fat percentage, and a high average HbA1c level was found when compared to our study 41 . Similarly, the subscapular skinfold thickness has been suggested as a potentially useful screening tool to measure the risk of becoming obese in female adults 42 …”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…To date, only one cross‐sectional study done in China has reported the association between HbA1c and body fat percentage in T2DM patients on insulin therapy. In this study, a Jawon bioelectrical impedance analyzer (BIA) was used to measure body fat percentage, and a high average HbA1c level was found when compared to our study 41 . Similarly, the subscapular skinfold thickness has been suggested as a potentially useful screening tool to measure the risk of becoming obese in female adults 42 …”
Section: Discussionmentioning
confidence: 51%
“…In this study, a Jawon bioelectrical impedance analyzer (BIA) was used to measure body fat percentage, and a high average HbA1c level was found when compared to our study. 41 Similarly, the subscapular skinfold thickness has been suggested as a potentially useful screening tool to measure the risk of becoming obese in female adults. 42 To date, we could not find the studies reporting the effects of body fat percentage or subscapular skinfold thickness to HbA1c or 1-h 50 g GCT in screening GDM in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…However, elevated BF% is not included in conditions recommended for screening T2D in the Chinese guideline ( 20 ). Of note, a cross-sectional study conducted by Ruan et al with 85 T2D patients in China, indicated that reducing body fat was an important adjuvant therapy to improve glycemic control among T2D patients with high body fat ( 42 ). Therefore, cost-effective actions to maintain appropriate body fat levels and preventing diabetes, such as specific nutrition education, clinical application of BF% based on sex, and lifestyle intervention included targeting diet and physical activity, are meaningful to take to reduce the disease burden related to T2D in the Chinses healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…Self-monitoring of blood glucose (SMBG) is an integral component of diabetes management that aims to improve glycemic control and decrease the risk of diabetes-related complications. [1][2][3] Blood glucose monitoring system (BGMS), including real-time continuous glucose monitoring (CGM) and intermittently scanned CGM (also known as flash continuous glucose monitoring systems, FCGM), can provide continuous measurements of glucose levels and thereby aid diabetes patients in the adjustment of their diet, physical activity, and treatment regimen. 4,5 Any error in the BGMS, including slight inaccuracies in the measurements, could adversely affect patient care and treatment.…”
Section: Introductionmentioning
confidence: 99%